Research of mechanical properties of thermite material on the basis of steel dross - Rud V.; Saviuk I.; Samchuk L.; Povstyana Y. (Журнал інженерних наук)
Important direction in the development of technologies for the recycling of wastes of industrial productions is inclination on the use energy saving technologies. The article deals with general aspects of methods of utilization of industrial wastes by methods of powder metallurgy. One of the same methods, which is highly effective and technologically, is the method of utilization of dross by using it as the main component of exothermic mixtures. On the basis of experimental research composition of exothermic charge based on the scale of steel was developed and proposed that can be used for surfacing the details of responsible designation. The choice of main and alloying components of charge was conducted on the analysis of literature data and the calculation of the required chemical characteristics of the material. According to the chemical composition, the termite material can be attributed to qualitative structural steels. Important characteristic of this material is the lack of content of harm fulimpurities, such as sulfur and phosphorus. Research of mechanical properties showed that material has a high resilient deformationon a compression and durability. The analysis of diagram deformation allows to assert that plastic decomposition prevails upon the destruction of the material. The hardness of material at different depths of sampling is different, which indictates the impact of the technological parameters of combustion of exothermic mixtures on the properties of the material. Investigation of impact strength showed that the change in the temperature of the test does not significantly affect its change, which indictates the suitability of the developed termite steel for the surfacing of parts working under reverse friction and shock loads.